CD8+ recent thymic emigrants exhibit increased responses to low affinity ligands and improved access to peripheral sites of inflammation - Berkley, Amy M. (2014)
To explore the TCR sensitivity of recent thymic emigrants (RTEs), we triggered T cells with altered peptide ligands (APLs). Upon peptide stimulation in vitro, RTEs exhibited increased TCR signal transduction, and following infection in vivo with APL-expressing bacteria, CD8 RTEs expanded to a greater extent in response to low affinity antigens than their mature T cell counterparts. RTEs skewed to short-lived effector cells in response to all APLs but were also characterized by diminished cytokine production. RTEs responding to infection expressed increased levels of VLA-4, with consequent improved entry into inflamed tissue and pathogen clearance. These positive outcomes were offset by the capacity of RTEs to elicit autoimmunity. Overall, salient features of CD8 RTE biology should inform strategies to improve neonatal vaccination and therapies for cancer and HIV, as RTEs make up a large proportion of the T cells in lymphodepleted environments.